2017
DOI: 10.1080/09593330.2017.1301564
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific interaction of trihalomethane (THM) precursors in a scaled-up distribution network using response surface methodology (RSM)

Abstract: Response surface methodology (RSM) with central composite design (CCD) was used to monitor and optimize species-specific interaction of trihalomethane (THM) precursors in a scaled-up distribution network (DN). Independent variables such as applied chlorine (Cl), contact time (t), humic acid (HA) and bromide ions (Br) were analyzed using full factorial CCD. Analysis of variance revealed a good agreement between experimental data and proposed a two-factor interaction model (p = .04, R = 0.7983). As a precursor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The increased formation of tTHMs in the presence of NaOCl is likely a result of the higher pH of the disinfectant (11.4 ± 0.1) compared to HOCl (5.6 ± 0.25) or ECAS (3.3 ± 0.16). THMs have shown to have a greater formation affinity in more alkaline conditions (Peters et al, 1980;Urano et al, 1983;Brown et al, 2010;Saidan et al, 2013;Rasheed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased formation of tTHMs in the presence of NaOCl is likely a result of the higher pH of the disinfectant (11.4 ± 0.1) compared to HOCl (5.6 ± 0.25) or ECAS (3.3 ± 0.16). THMs have shown to have a greater formation affinity in more alkaline conditions (Peters et al, 1980;Urano et al, 1983;Brown et al, 2010;Saidan et al, 2013;Rasheed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HOCl ⇋ OCl − +H + pKa = 7.5 (7) (Liu and Margerum, 2001;Heeb et al, 2014) THMs have been shown to have a greater affinity to form at a higher pH and with increased free chlorine concentrations (Peters et al, 1980;Urano et al, 1983;Brown et al, 2010;Saidan et al, 2013;Rasheed et al, 2017). It is known that HOCl is the dominant compound that results in tTHM formation, although, since tTHM formation is base-catalyzed (Yee et al, 2009), there is a trade-off in terms of the effect of pH.…”
Section: Disinfectants Ecas Hocl Naocl H H H H H H H H H H H H H H H mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the fitted regression equation showed a satisfactorily good fit for the model applicability. It also implies that errors are distributed normally (Sagbas, 2011; Appavoo et al ., 2014; Rasheed et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Process optimization is an important step in deciding the optimum range of variables that would maximize the output response (Rasheed et al ., 2018). Based on the variables selected, numerical optimization was performed as an optimizing steps to achieve maximum bacterial inactivation whilst minimum DBPs formation in the system, expressed a desirability value (D), a value closer to 1 is considered to be desirable and significant by the software (Umar et al ., 2011).…”
Section: Resultsmentioning
confidence: 99%